ANALYZING OF INVESTMENT DECISIONS IN THE SRI KEHATI INDEX - Vicly Gunawan Lumingkewas; Kartika Nuringsih (Graduate Program of Universitas Tarumanagara, 2024)
This study aims to find out and analyze the influence of profitability, market growth and risk rate on investment decision. The research method used was purposive sampling with a total sample of 15 companies listed in SRI KEHATI Index. This study divided the years of observation into 3 periods observation, first period 2017-2019, second period 2020-2022, and the overall periode 2017-2022. The type of data was secondary data and was obtained from annual financial statements. Data analysis methods used are descriptive statistical tes, classical assumption analysis, partial test, simultaneous test, and test coefficient of determination. Based on the result of testing the hypothesis 2017-2019 period show that partially profitability has significant effect on investment decision, while market growth and risk rate have no significant effect on investment decision. For the second and overall period show that patially profitability, market growth and risk rate have no significant effect on investment decision. The results of the study are a consideration in understanding investment decisions related to sustainability issues, especially the Sri Kehati index.